The Role of Anethum graveolens L. (Dill) in the Management of Diabetes - Mohammad Taghi Goodarzi; Iraj Khodadadi; Heidar Tavilani; Ebrahim Abbasi Oshaghi (Journal of Tropical Medicine)
Aim. There is evidence that Anethum graveolens (AG) has been used for centuries in Asian traditional medicine, and its constituents have useful effects on the control and management of diabetes and cardiovascular disorders. AG has many useful effects, including hypolipidemic and hypoglycemic effects, and it has been reported to reduce the incidence of diabetic complications. It acts mainly by affecting antioxidant capacity and change in some genes in glucose and lipid pathways. The aim of the present paper was to summarize pharmacological effects of AG in the management of diabetes. Methods. To prepare this review, a pharmacological and phytochemical literature survey was performed using Scopus, PubMed, and Web of Science. Also, some historical and ethnopharmacological literature sources were used. Results. This review plans to provide readers with an assessment of the pharmacological effects of AG, especially in diabetes. Conclusion. The paper highlights the therapeutic effects of AG which would aid in supporting their safe use in the management of diabetes and cardiovascular diseases.